Resistance to infection with Eimeria vermiformis in mouse radiation chimeras is determined by donor bone-marrow cells. - Joysey, H S (1988)
The course of infection with Eimeria vermiformis was determined in BALB/b, BALB/c, and C57BL/10ScSn (B10) mice and in radiation chimeras prepared from the H-2-compatible BALB/b and B10 mice. The BALB strains, irrespective of H-2 haplotype, were resistant, the B10 mice were susceptible, and in the chimeras infection was characterized by the genotype of the donated bone-marrow cells and not by the phenotype of the recipient. Thus, the genetic control of relative resistance or susceptibility to infection with this parasite is expressed through bone-marrow-derived cells.